Cholinesterase inhibitory, anti-amyloidogenic and neuroprotective effect of the medicinal plant Grewia tiliaefolia - An in vitro and in silico study - Dicson Sheeja Malar; Rajamohamed Beema Shafreen; Shunmugiah Karutha Pandian; Kasi Pandima Devi (Taylor & Francis Group, 2017)
Context: Grewia tiliaefolia Vahl. (Tiliaceae) is a sub-tropical plant used as an indigenous medicine in India. However, its efficacy has not been evaluated against Alzheimer's disease. Objectives: The objective of this study is to evaluate cholinesterase inhibitory, anti-aggregation and neuroprotective activity of G. tiliaefolia. Materials and method: Grewia tiliaefolia leaves were collected from Eastern Ghats region, India, and subjected to successive extraction (petroleum ether, chloroform, ethyl acetate, methanol and water). The extracts were subjected to in vitro antioxidant, anticholinesterase and anti-aggregation assays. The active methanol extract (MEGT) was separated using column chromatography. LC-MS analysis was done and the obtained compounds were docked against acetylcholinesterase (AChE) enzyme to identify the active component. Results: Antioxidant assays demonstrated that the MEGT showed significant free radical scavenging activity at the IC50 value of 71.5 ± 1.12 μg/mL. MEGT also exhibited significant dual cholinesterase inhibition with IC50 value of 64.26 ± 2.56 and 54 ± 0.7 μg/mL for acetyl and butyrylcholinesterase (BChE), respectively. Also, MEGT showed significant anti-aggregation activity by preventing the oligomerization of Aβ25-35. Further, MEGT increased the viability of Neuro2a cells up to 95% against Aβ25-35 neurotoxicity. LC-MS analysis revealed the presence of 16 compounds including vitexin, ellagic acid, isovitexin, etc. In silico analysis revealed that vitexin binds effectively with AChE through strong hydrogen bonding. These results were further confirmed by evaluating the activity of vitexin in vitro, which showed dual cholinesterase inhibition with IC50 value of 15.21 ± 0.41 and 19.75 ± 0.16 μM for acetyl and butyrlcholinesterase, respectively. Discussion and conclusion: Grewia tiliaefolia can be considered as a promising therapeutic agent for the treatment of AD.